2005
DOI: 10.1002/eji.200425715
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cell contributions to allergen induced pulmonary inflammation and airway hyperreactivity

Abstract: The pathogenesis of asthma has been linked to the production of type 2 cytokines, which can be expressed by several cell types in the lung. These studies investigated CD8 + T cell responses in a murine cockroach antigen (CRA) model of asthma. The results from these present studies show that depletion of CD8 + T cells after allergen sensitization to CRA significantly reduces airway hyperreactivity, airway eosinophilia and pulmonary type 2 cytokine levels. The data demonstrate that CD8 + T cells from CRA-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 44 publications
4
29
0
2
Order By: Relevance
“…Some of these effects are associated with (food) allergy and suggest that the whey hydrolysate does sensitize against whey, which is in line with the detected increased IgE levels. This includes an increased percentage of (activated) Thelper cells and a decreased percentage of cytotoxic T cells [42,43], together with an increase in activated Th2 cells [44]. The fact that despite this established sensitization no clinical symptoms were observed, suggests a stimulated immune regulatory effect of the whey hydrolysate.…”
Section: Discussionmentioning
confidence: 97%
“…Some of these effects are associated with (food) allergy and suggest that the whey hydrolysate does sensitize against whey, which is in line with the detected increased IgE levels. This includes an increased percentage of (activated) Thelper cells and a decreased percentage of cytotoxic T cells [42,43], together with an increase in activated Th2 cells [44]. The fact that despite this established sensitization no clinical symptoms were observed, suggests a stimulated immune regulatory effect of the whey hydrolysate.…”
Section: Discussionmentioning
confidence: 97%
“…Our protocol used injections of the whole splenic T-cell population collected from DO11.10 mice, based in large part on the fact that multiple subsets of T cells, including CD4 ϩ T cells, CD8 ϩ T cells, 32 and iNKT cells, 33 are critically involved in modulating allergic asthma. The pan-T-cell "strategy" was even more relevant after we found that splenic T cells in DO11.10 donor mice were CD4 ϩ , CD8 ϩ , or double negative.…”
Section: Discussionmentioning
confidence: 99%
“…Increased numbers of CD8+ T cells in the BAL and HLN at LIT also correlated with the resolution of airway inflammation. Suppressor CD8+ T cells have been shown to be important in the regulation of many immune responses, including airway inflammation [43,44,45]. Additionally, B cells have suppressive activity in numerous mouse models [46], including allergic airway inflammation [47, 48].…”
Section: Discussionmentioning
confidence: 99%